PENGEMBANGAN KAWASAN WISATA PENTADIO RESORT DENGAN PENDEKATAN ARSITEKTUR TROPIS MODERN - Naway, Alpian; Algiffari, M. Fauzhan; Ajami, Frans Mitran (Program Vokasi Universitas Negeri Gorontalo, 2023)
The development of tourist objects will certainly contribute to the growth of the area around these tourist objects. Until now, Gorontalo Province has many tourist objects whose development has not received much attention so that it can cause a reduction in visitors to these tours, one of which is the Pentadio Resort which has an area of 14 ha and is located in Gorontalo Regency. The specialty of the Pentadio Resort tour is the hot spring bath and visitors can witness the bursts of hot springs. However, the current condition of the Pentadio Resort Hot Springs area is very concerning, the local community is not able to optimally utilize and manage these potentials as well as the lack of attention from the Government and the lack of other supporting facilities such as children's playgrounds that are not well organized. This research aims to create a tourist destination design that applies the concept of modern tropical architecture by improving the quality of tourist facilities such as accommodation, recreational and entertainment facilities. This study uses qualitative methods and observations as a first step in determining aspects of the design concept for the development of tourist areas. The analytical method applied is micro analysis of the site planning site and macro analysis is determining the criteria for site analysis in the area. The final result of this study is the application of modern tropical architectural concepts to sustainable natural tourism areas. The results of the study show that there are 3 concepts for the development of spatial design visualization in the pentadio resort tourism area, namely the core zone, buffer zone, and service zone. Development in this area can meet the needs of visitors and create open spaces that are comfortable, safe, fun, cultured in the development of pentadio resort tourism.